Clinical and Molecular Features of Anti-CENP-B Autoantibodies - Rahul M. Prasad; Alfonso Bellacosa; Tim J. Yen (MDPI AG, 2021)
Centromeric proteins are the foundation for assembling the kinetochore, a macromolecular complex that is essential for accurate chromosome segregation during mitosis. Anti-centromere antibodies (ACAs) are polyclonal autoantibodies targeting centromeric proteins (CENP-A, CENP-B, CENP-C), predominantly CENP-B, and are highly associated with rheumatologic disease (lcSSc/CREST syndrome). CENP-B autoantibodies have also been reported in cancer patients without symptoms of rheumatologic disease. The rise of oncoimmunotherapy stimulates inquiry into how and why anti-CENP-B autoantibodies are formed. In this review, we describe the clinical correlations between anti-CENP-B autoantibodies, rheumatologic disease, and cancer; the molecular features of CENP-B; possible explanations for autoantigenicity; and, finally, a possible mechanism for induction of autoantibody formation.